Lupus nephritis with visual field defect secondary to hypertensive retinopathy: a case report - Hor, SM; Norshamsiah Md Din,; Mushawiahti Mustapha,; Hazlita Mohd Isa, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
A 23-year-old lady presented with both eye progressive painless blurring of vision for two weeks in 2011. Prior to that she had malar rash, hair loss, photosensitivity and bilateral leg swelling. Ocular examination showed that visual acuity on the right was 6/60 and on the left was 6/24. Both optic disc were swollen with extensive peripapillary cotton wool spot (CWS), flame shape haemorrhages, dilated and tortuous vessels with macular oedema. Systemic examination revealed blood pressure of 176/111 mmHg, malar rash and alopecia. Diagnosis of grade 4 hypertensive retinopathy secondary to SLE was made. The diagnosis was confirmed by positive ANA/ dsDNA, low C3/ C4 and renal biopsy showed lupus nephritis. She was treated with oral prednisolone, hydroxychloroquine and cyclosporin A. Throughout the monitoring for hydroxychloroquine toxicity, vision over both eyes were 6/9, but serial visual fields showed non-progressive left superior and inferior scotoma while right eye showed inferior scotoma. The intraocular pressure was normal with pink optic disc and cup disc ratio of 0.3. Optical coherence tomography (OCT) showed temporal and nasal retinal nerve fiber layer thinning bilaterally. However, macula OCT, fundus fluorescein angiography and autofluorescence were normal. The visual field defect was concluded secondary to CWS indicating microinfarction of the retinal nerve fiber secondary to previous hypertensive retinopathy. Non-progressive visual field defects may occur after the appearance of CWS in hypertensive retinopathy and it should not be overlooked when diagnosing glaucoma or hydroxychloroquine toxicity.